Biometric Identification: Face Recognition based on Iris Detection - Mohd Rizon, Mohd Juhari, Prof. Madya Dr.; R. Badlishah, Ahmad, Prof. Madya Dr.; Ahmad Nasir, Che Rosli (International Exhibition of Inventions, 2010)
Prof. Madya Dr. Mohd Rizon and his team won silver at International Exhibition of Inventions of Geneva 2006, 5th - 9th April 2006 was held at Palexpo, Geneva, Switzerland.